LOVE, NATURE AND THE CITY. THE INFLUENCE OF ÉMILE VERHAEREN ON THE WORKS OF TAKAMURA KŌTARŌ. - Sonnenberg, Katarzyna (Porównania, 2016)
French poetry, painting and sculpture inspired a great number of Japanese artists gathered around Pan no Kai (The Pan Society). One of them was Takamura Kōtarō (1883-1956), a poet and sculptor, well known for his love poems addressed to his wife Chieko and collected in the volume Chieko shō. The article is an attempt to analyse the impact the life and work of Émile Verhaeren, Belgian poet writing in French and famous representative of French symbolism, had on Takamura’s oeuvre, especially with regards to his love poetry and images of nature and city.